PRIORITY DIRECTIONS FOR DEVELOPING THE CAPACITY OF THE AGRICULTURAL SECTOR OF THE REPUBLIC OF UZBEKISTAN - Bekmirzayev Mirzoxid Adashalieyich (Scholar Express Journals, 2026)
This article discusses the possibilities of sustainable development of agriculture in ensuring the economic security of our country, the effective use of the potential of the agricultural sector, its priority areas. The factors determining the sustainable development of agriculture, the main content and results of economic reforms being implemented in the agricultural sector are described. Scientific proposals and practical recommendations aimed at the prospects for the development of agricultural sectors in our republic are developed.
Keywords: State; economic security; agriculture; factors